Serum microRNAs in patients with genetic amyotrophic lateral sclerosis and pre-manifest mutation carriers. (5th September 2014) - Freischmidt, Axel; Müller, Kathrin; Zondler, Lisa; Weydt, Patrick; Volk, Alexander E.; Božič, Anže Lošdorfer; Walter, Michael; Bonin, Michael; Mayer, Benjamin; von Arnim, Christine A. F.; Otto, Markus; Dieterich, Christoph; et al.
Abstract : Little is known about the preclinical phase of amyotrophic lateral sclerosis (ALS). Freischmidt et al. reveal strikingly similar microRNA profiles in patients with familial ALS and pre-manifest mutation carriers, with specific microRNAs downregulated largely independently of the causative mutations. The possibility of presymptomatic disease modifying treatment should be investigated in ALS. Abstract : Knowledge about the nature of pathomolecular alterations preceding onset of symptoms in amyotrophic lateral sclerosis is largely lacking. It could not only pave the way for the discovery of valuable therapeutic targets but might also govern future concepts of pre-manifest disease modifying treatments. MicroRNAs are central regulators of transcriptome plasticity and participate in pathogenic cascades and/or mirror cellular adaptation to insults. We obtained comprehensive expression profiles of microRNAs in the serum of patients with familial amyotrophic lateral sclerosis, asymptomatic mutation carriers and healthy control subjects. We observed a strikingly homogenous microRNA profile in patients with familial amyotrophic lateral sclerosis that was largely independent from the underlying disease gene. Moreover, we identified 24 significantly downregulated microRNAs in pre-manifest amyotrophic lateral sclerosis mutation carriers up to two decades or more before the estimated time window of disease onset; 91.7% of the downregulated microRNAs in mutation carriers overlapped with the patients with familial amyotrophic lateral sclerosis. Bioinformatic analysis revealed a consensus sequence motif present in the vast majority of downregulated microRNAs identified in this study. Our data thus suggest specific common denominators regarding molecular pathogenesis of different amyotrophic lateral sclerosis genes. We describe the earliest pathomolecular alterations in amyotrophic lateral sclerosis mutation carriers known to date, which provide a basis for the discovery of novel therapeutic targets and strongly argue for studies evaluating presymptomatic disease-modifying treatment in amyotrophic lateral sclerosis.